A Positive Regulator of Nodule Organogenesis, NODULE INCEPTION, Acts as a Negative Regulator of Rhizobial Infection in Lotus japonicus. Issue 2 (10th April 2014) - Yoro, Emiko; Suzaki, Takuya; Toyokura, Koichi; Miyazawa, Hikota; Fukaki, Hidehiro; Kawaguchi, Masayoshi
Abstract : A transcription factor, known as a positive regulator of nodule organogenesis in root cortex, acts as a negative regulator of epidermal infection events by rhizobia . Abstract: Legume-rhizobium symbiosis occurs in specialized root organs called nodules. To establish the symbiosis, two major genetically controlled events, rhizobial infection and organogenesis, must occur. For a successful symbiosis, it is essential that the two phenomena proceed simultaneously in different root tissues. Although several symbiotic genes have been identified during genetic screenings of nonsymbiotic mutants, most of the mutants harbor defects in both infection and organogenesis pathways, leading to experimental difficulty in investigating the molecular genetic relationships between the pathways. In this study, we isolated a novel nonnodulation mutant, daphne, in Lotus japonicus that shows complete loss of nodulation but a dramatically increased numbers of infection threads. Characterization of the locus responsible for these phenotypes revealed a chromosomal translocation upstream of NODULE INCEPTION ( NIN ) in daphne . Genetic analysis using a known nin mutant revealed that daphne is a novel nin mutant allele. Although the daphne mutant showed reduced induction of NIN after rhizobial infection, the spatial expression pattern of NIN in epidermal cells was broader than that in the wild type. Overexpression of NIN strongly suppressed hyperinfection in daphne, and daphne phenotypes were partially rescued by cortical expression of NIN . These observations suggested that the daphne mutation enhanced the role of NIN in the infection pathway due to a specific loss of the role of NIN in nodule organogenesis. Based on these results, we provide evidence that the bifunctional transcription factor NIN negatively regulates infection but positively regulates nodule organogenesis during the course of the symbiosis.